CADANGAN KARBON PADA TEGAKAN POHON HUTAN KOTA DI TAMAN MARGASATWA RAGUNAN DKI JAKARTA - Mia Azizah; Nia Yuliani; Heriyanto Heriyanto (Florea : Jurnal Biologi dan Pembelajarannya, 2019)
Increase environmental problems, such as air pollution and temperatures increase in DKI Jakarta, make the existence of urban forests very important. Trees have an important role becausethey function as the most efficient carbon sink and storage in urban areas. Along with theincreasing number of visitors carrying vehicles, the higher the potential for air pollution in Ragunan Wildlife Park (TMR). The objectives of this study are: To analyze the community structure of tree species that have potential carbon stocks, and estimate carbon stocks stored in tree trunks. The study was conducted in four regions (north, west, east, south) Ragunan WildlifePark, DKI Jakarta. Vegetation analysis was carried out by calculating the Important Value Index (INP), and carbon stock analysis was carried out through the Allometric approach. The highest INP value was mahoni (Swietinia macrophylla) amounting to 45.51%, cengal pasir (Hopeaodorata) 33.31%, and dao (Dracontomelon dao) 28.26%. The largest amount of carbon reserves is found in the western region, which is 52,503 kg / ha, and the largest contribution of carbon stocks is from dao trees (Dracontomelon dao) of 30,091 kg / ha, cengal sand 25,372 kg / ha, oilpalm (Elaeis guinensis).